Optimizing Pocket Money as a Financial Learning Medium for Early Childhood: An Educational Approach in Duku Sebetok, Galangpengampon Village - Adyuta, Setyadan; Fasihullisan, M Daffa; Prakoso, Satria Gigih; Khoiruzidan, Muhammad; Anah, Rizky; Setyawan, M Ghilang Maulud; Permadi, Yulian Wahyu (Urecol Journal. Part A: Education and Training, 2025)
Financial literacy is a fundamental skill that should be instilled from an early age to shape students into independent and responsible individuals. Many fifth-grade students at MII Kyai Betoro, totalling 14, still lack adequate knowledge of money management, putting them at risk of developing consumerist habits. The issue became the focus of a Community Service Program in Dukuh Sebetok, Galangpengampon Village, Wonopringgo District, through the “Smart Spending” program, which aimed to introduce basic money management concepts early on. The program employed educational approaches such as simulations, group discussions, and pre- and post-assessment. The results showed an increase in students' understanding of saving concepts from 42% to 78% after the program implementation. These findings emphasize the importance of early financial education and the support of both schools and families.